1994
DOI: 10.1248/bpb.17.1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy of Cerebrospinal Fluid as an Aid in Neurological Diagnosis.

Abstract: The proton magnetic resonance (1H-NMR) spectra were obtained from 38 cerebrospinal fluid (CSF) samples from 34 patients with various central nervous system (CNS) diseases and the H2O signals were reduced by the presaturation method. A doublet signal for CH3 protons of lactate, as well as a singlet one for alpha-CH proton of glucose, were clearly detected in all the spectra obtained. The relative lactate concentration values were calculated on the basis of the glucose concentrations which had been measured by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1994
1994
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Matthews et al assessed the methabolic reason of encephalopathy associated with acute bacterial meningitis using Phosphorus magnetic resonance spectroscopy in conjunction with characterizing the changes of magnetic resonance spectroscopy signals during bacterial meningitis (24). The results of Phosphorus MR spectroscopy indicated the extracellular acidosis that were compatible with results of other studied which are reported in this review (19,23,14). (24).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Matthews et al assessed the methabolic reason of encephalopathy associated with acute bacterial meningitis using Phosphorus magnetic resonance spectroscopy in conjunction with characterizing the changes of magnetic resonance spectroscopy signals during bacterial meningitis (24). The results of Phosphorus MR spectroscopy indicated the extracellular acidosis that were compatible with results of other studied which are reported in this review (19,23,14). (24).…”
Section: Discussionsupporting
confidence: 65%
“…Also in bacterial meningitis during therapy it decreases accompanied by favorable changes in the clinical response to treatment, as demonstrated by a reduction in the levels of CSF protein and CSF cell count (14).…”
Section: Discussionmentioning
confidence: 99%
“…28,33,34,61 It has recently been observed that the analysis of CSF based on CSF cytology, sugar and protein content is not the primary information to serve for the purpose of differential diagnosis. 25 As noted during the PROTON MR CSF ANALYSIS 221 course of our present investigation, in certain cases, clinical symptoms (as observed by the clinician) were difficult to interpret and it was found that the children were unable to express themselves.…”
Section: Discussion Nmr Spectroscopic Findings and Clinical Observationsmentioning
confidence: 99%
“…28 In recent times, high-resolution proton MR spectroscopy has beyond doubt become one of the most important analytical tools for obtaining metabolic information on biological fluid or tissue extracts. [28][29][30][31][32][33][34][35][36][37][38][39] It has been well documented that NMR spectroscopy gives non-invasive, qualitative and quantitative information regarding the metabolic profile [40][41][42][43][44][45][46][47][48][49][50][51][52] and usually a metabolite concentration of greater than a few mM is detectable in 1 H NMR spectra 53 in a reasonable amount of time ( 1 H NMR; 128 scans; approximately 15 min), and with the recent technological advances in NMR probe design such as microprobes and cryoprobes, the detection range and time taken have been reduced further using high-field magnets, 600 MHz or higher. The potential advantages of NMR and the persistent problems regarding the timely diagnosis of childhood meningitis have prompted us to explore 1 H NMR spectroscopy as a diagnostic utility based on the analysis of CSF from 191 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Such metabolomic methods can detect genotypic and phenotypic differences even in closely related microorganisms and also in genetically modified strains [13][14][15][16][17], with greater discriminatory power than transcriptomics and proteomics [17,18]. Spectroscopic techniques characterise rapidly and simultaneously multiple chemical compounds in biological fluids [10,[19][20][21][22][23][24][25][26][27][28]. In addition, NMR spectroscopy detects low molecular weight metabolites, requires no time-consuming sample preparation and is non-destructive.…”
Section: Introductionmentioning
confidence: 99%